MoAlB alloy material in high temperature liquid lead-bismuth environment and preparation method thereof

By optimizing in the preparation process of MoAlB alloy materials, the problem of insufficient corrosion resistance of liquid lead-bismuth fast stack materials in high temperature and high pressure environments is solved, and the effect of low corrosion rate and high stability is achieved.

CN118880141BActive Publication Date: 2025-04-04SHANGHAI JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410927087.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-11
Publication Date
2025-04-04
Estimated Expiration
2044-07-11

AI Technical Summary

Technical Problem

The corrosion resistance, stability and service life of liquid lead-bismuth fast reactor fuel assembly structural materials in high temperature and high pressure environments are insufficient, and cannot meet performance requirements.

Method used

MoAlB alloy material is used to optimize the uniformity and microstructure of the alloy through specific alloy composition design and preparation processes, including smelting, heat treatment and mechanical molding, and improve its corrosion resistance in high-temperature liquid lead-bismuth.

Benefits of technology

The low corrosion rate and high stability of MoAlB alloy materials in high-temperature liquid lead-bismuth are achieved, which improves its performance in harsh environments and has good application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118880141B_ABST
    Figure CN118880141B_ABST
Patent Text Reader

Abstract

The present invention discloses a MoAlB alloy material in a high-temperature liquid lead-bismuth environment and a preparation method thereof, and belongs to the technical field of nuclear materials. The chemical components in the MoAlB alloy material of the present invention are calculated by mass, including: 45‑55 parts of Mo, 25‑35 parts of Al and 5‑8 parts of B. The present invention improves the uniformity of the alloy material and optimizes the microstructure through improvements in the preparation process. The heat treatment step further stabilizes the microstructure of the alloy and improves its corrosion resistance. The present invention achieves low corrosion rate and high stability of the MoAlB alloy material in high-temperature liquid lead-bismuth through specific alloy component design and preparation process. By optimizing the composition and microstructure of the alloy, the performance of this alloy material in harsh environments is improved, and it has good application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nuclear materials, and in particular to a MoAlB alloy material in a high-temperature liquid lead-bismuth environment and a preparation method thereof. Background Art

[0002] Nuclear energy is regarded as the key to energy transformation due to its advantages such as low carbon emissions, high efficiency, reliability and stability. Against this background, the fourth-generation nuclear energy systems, including ultra-high temperature gas-cooled reactors, lead-cooled reactors, molten salt reactors, etc., are being developed simultaneously. Among the many fourth-generation nuclear reactors, the lead-bismuth eutectic-cooled fast reactor (LBFR) using liquid lead-bismuth eutectic (LBE) as coolant has received special attention. Compared with traditional coolants such as sodium (Na) and sodium-potassium alloy (NaK), lead-bismuth eutectic coolant has a longer service life, higher efficiency, smaller size and higher safety due to its high boiling point, low reaction with water and air, and good radiation shielding properties.

[0003] However, a major challenge facing LBFR is that liquid lead-bismuth alloy is highly corrosive to steel, which greatly limits the operating temperature of LBFR, thus affecting its operating efficiency and safety.

[0004] Currently, austenitic stainless steel is used as the container material in lead-cooled reactors, and its operating temperature is limited to below 500°C. However, in order to improve the economy of the reactor, it is necessary to increase the operating temperature of molten lead / lead-bismuth to improve power generation efficiency. This means that the internal LBE needs to operate at a higher temperature (600-1000°C) to achieve higher power and efficiency. This temperature range is significantly beyond the application range of traditional metal structural materials (such as 316L stainless steel, T91 steel, F / M steel, etc.).

[0005] The liquid lead-bismuth fast reactor fuel assembly structural materials in the existing technology still have certain deficiencies in corrosion resistance, stability, service life, etc. under high temperature and high pressure environments, cannot meet performance requirements, and there is room for further improvement. Summary of the invention

[0006] The object of the present invention is to provide a MoAlB alloy material in a high-temperature liquid lead-bismuth environment and a preparation method thereof to solve the above-mentioned problems in the background technology. The present invention improves the uniformity of the alloy material and optimizes the microstructure through improvements in the preparation process. The heat treatment step further stabilizes the microstructure of the alloy and improves its corrosion resistance. The present invention achieves low corrosion rate and high stability of the MoAlB alloy material in high-temperature liquid lead-bismuth through specific alloy component design and preparation process. By optimizing the composition and microstructure of the alloy, the performance of this alloy material in harsh environments is improved, and it has good application value.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] One of the technical solutions of the present invention is to provide a MoAlB alloy material, wherein the chemical components in the MoAlB alloy material are calculated by weight and include:

[0009] Mo 45-55 parts, Al 25-35 parts and B 5-8 parts.

[0010] Preferably, in the MoAlB alloy material, the mass percentage of P is ≤0.001%, the mass percentage of S is ≤0.002%, and the mass percentage of O is ≤0.002%.

[0011] The second technical solution of the present invention is to provide a method for preparing the above-mentioned MoAlB alloy material, comprising the following steps:

[0012] The elements are mixed in proportion, smelted, and an ingot is obtained;

[0013] The ingot is subjected to heat treatment and mechanical forming treatment to obtain the MoAlB alloy material.

[0014] Preferably, the smelting temperature is 1200-1500° C., and the smelting is performed under a protective atmosphere.

[0015] Preferably, the heat treatment is carried out at a temperature of 800-1000° C. and for a time of 1-5 h.

[0016] Preferably, the mechanical forming process comprises forging, rolling or extrusion.

[0017] The third technical solution of the present invention is to provide an application of the above-mentioned MoAlB alloy material in a nuclear reactor coolant system.

[0018] A fourth technical solution of the present invention is to provide a nuclear reactor coolant system, wherein the cooling pipes and / or heat exchangers in the nuclear reactor coolant system are prepared using the above-mentioned MoAlB alloy material as raw material.

[0019] The beneficial technical effects of the present invention are as follows:

[0020] The small amount of dissolved oxygen in LBE tends to migrate and diffuse spontaneously to the surface of MoAlB, but due to the preferential oxidation of Al, a thin layer of aluminum oxide will form on the surface of MoAlB, thus playing a protective role. Over time, after the surface Al oxide layer is exhausted, a Mo-rich oxide layer will form under the aluminum oxide layer.

[0021] Studies have shown that it is difficult for Pb and Bi to replace Al element in the lattice of the MoAlB alloy material of the present invention to form chemical reaction corrosion, thus forming the thermodynamic basis for MoAlB to resist LBE corrosion.

[0022] The present invention improves the uniformity of the alloy material and optimizes the microstructure by improving the preparation process. In the smelting process, inert gas protection is used to avoid oxidation, thereby ensuring the purity of the alloy. The heat treatment step further stabilizes the microstructure of the alloy and improves its corrosion resistance.

[0023] The present invention realizes low corrosion rate and high stability of MoAlB alloy material in high-temperature liquid lead-bismuth through specific alloy component design and preparation process. By optimizing the composition and microstructure of the alloy, the performance of the alloy material in harsh environment is improved, and it has good application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is the SEM image of the product in Example 1.

[0026] Figure 2 The XRD patterns of the a-side and b-side of the product of Example 1 are shown in Figure 1, where (a) is the a-side and (b) is the b-side.

[0027] Figure 3 The backscattered photo and EDS element distribution diagram of the interface of the product after corrosion in Example 1. Among them, (a) is a backscattered photo, and (b)-(f) are EDS element distribution diagrams of Pb, Bi, Mo, Al and O elements.

[0028] Figure 4 The TEM photo, EDX element distribution map and EDX spectrum of the interface after corrosion of the product in Example 1. Among them, (a) is a TEM photo, (b)-(f) are EDX element distribution maps of Pb, Bi, Mo, Al and O elements, and (g) is an EDX spectrum.

[0029] Figure 5 The SEM images and EDS element distribution diagrams of the interface of 316L stainless steel after corrosion. Among them, (a) is the SEM image when LBE penetrates the oxide layer, (b) is the SEM image when LBE invades the matrix, and (c)-(f) are the EDS element distribution diagrams of Pb, Bi, Fe, Cr and O elements.

[0030] Figure 6 Schematic diagram of the protection principle of the product of Example 1 at different corrosion stages under LBE corrosion.

[0031] Figure 7 is the substitution energy of Pb and Bi elements replacing Al atoms in the lattice of the MoAlB alloy material of Example 1 and the formation enthalpy of the substitution compound. Wherein, (a) is the substitution energy; (b) is the formation enthalpy. DETAILED DESCRIPTION

[0032] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0033] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0035] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0036] All raw materials used in the following embodiments of the present invention are commercially available products.

[0037] Example 1

[0038] The chemical composition of MoAlB alloy material is calculated by mass:

[0039] Mo 50 parts, Al 30 parts and B 7 parts.

[0040] Preparation of MoAlB alloy material:

[0041] Melting: Mix the single powders of each element in proportion, and melt the mixed raw materials at a high temperature of 1200°C under argon protection until they are completely fused to obtain an ingot;

[0042] Heat treatment: The ingot was heat treated at 950 °C for 4 h and then naturally cooled to room temperature.

[0043] Mechanical processing: The heat-treated alloy material is processed into the required size and shape through forging and rolling processes to obtain MoAlB alloy material. The rolling process parameters are: rolling speed 0.5m / s, 6 rolling passes, reduction 5mm / pass, and rolling temperature 1000℃.

[0044] Figure 1 This is the SEM image of the product in Example 1.

[0045] Example 2

[0046] The chemical composition of MoAlB alloy material is calculated by mass:

[0047] Mo 45 parts, Al 25 parts and B 8 parts.

[0048] The specific preparation process is the same as that in Example 1.

[0049] Effect verification

[0050] (1) The textured microstructure of Example 1 was tested. The surface of the product of Example 1 in contact with the roller (denoted as surface a) and the surface perpendicular to the contact surface of the roller (denoted as surface b) were tested respectively. The XRD patterns of the two are shown in Fig. Figure 2 shown.

[0051] The formula for calculating the degree of texture is:

[0052] Among them, θ F is the relative dihedral angle of the texture degree, I hkl is the intensity of a given (hkl) peak, θ hkl is the angle between the (hkl) and (0k0) planes. F The higher the value, the greater the degree of texture.

[0053] It was measured that the θ in the rolling direction of the a surface F is 5°, and the angle θ of the rolling direction of the b surface F The a-side and b-side of the product of Example 1 form different textured microstructures through rolling.

[0054] Figure 2 The XRD diagrams of the a-side and b-side of the product of Example 1 are shown in Figure 1. (a) is the a-side and (b) is the b-side. Figure 2It can be seen that the diffraction peak intensity related to (020), (040), and (060) in (a) is much higher than that in (b). This is mainly because the preferred orientation formed after the material directly contacts the rolling roller is the texture orientation related to (020), (040), and (060).

[0055] (2) A vacuum / high-purity argon tube furnace equipped with an online trace oxygen content analyzer is used as a lead-bismuth static corrosion experimental system to conduct corrosion rate tests. The specific test process is as follows:

[0056] The sample of Example 1 was cut into 10×5×4.5 mm specimen strips, and the six surfaces of the specimen strips were ground and chamfered using 180#, 300#, 600#, 1800# and 3000# abrasive sandpapers in turn. The specimen strips were then fixed with molybdenum wire and placed in a corundum crucible. Then, smelted eutectic lead-bismuth alloy particles (lead 44.5wt.%, bismuth 55.5wt.%, melting point 123.5°C) were placed in the crucible. The molybdenum wire exposed outside the crucible was fastened with a stainless steel clamp to ensure that the sample was completely immersed in the molten lead-bismuth and would not float. The oxygen content in LBE was controlled at 10 -6 wt.%. Keep the temperature at 900℃ for 1000h, then take out the crucible after the furnace cools down. Use a flame spray gun to slightly bake the crucible surface. When the lead-bismuth alloy is completely melted, take out the sample. In order to avoid damaging the sample surface, rinse the sample with ethanol.

[0057] It has been measured that the corrosion rate of the alloy material in a liquid lead-bismuth environment at 900° C. is less than 1 micron / year.

[0058] (3) Corrosion resistance test

[0059] The MoAlB alloy material of Example 1 and commercially available 316L stainless steel were placed in a 900°C liquid lead-bismuth corrosion loop and subjected to a 1000-hour corrosion test. After the test, the morphology and element distribution of the alloy surface after corrosion were observed by surface analysis technology (scanning electron microscopy and energy dispersive X-ray spectroscopy). The test results are shown in Figure 2. Figure 3-5 shown.

[0060] Figure 3 The backscattered photo and EDS element distribution diagram of the interface of the product after corrosion in Example 1. Among them, (a) is a backscattered photo, and (b)-(f) are EDS element distribution diagrams of Pb, Bi, Mo, Al and O elements.

[0061] Figure 4The TEM photo, EDX element distribution map and EDX spectrum of the interface after corrosion of the product in Example 1. Among them, (a) is a TEM photo, (b)-(f) are EDX element distribution maps of Pb, Bi, Mo, Al and O elements, and (g) is an EDX spectrum.

[0062] Figure 4 (g) in is Figure 4 EDX spectrum of the red frame area (area #1) in (a).

[0063] Figure 5 The SEM images and EDS element distribution diagrams of the interface of 316L stainless steel after corrosion. Among them, (a) is the SEM image when LBE penetrates the oxide layer, (b) is the SEM image when LBE invades the matrix, and (c)-(f) are the EDS element distribution diagrams of Pb, Bi, Fe, Cr and O elements.

[0064] Figure 5 (a) and (b) are SEM images of the location where LBE penetrates the oxide layer and the location where LBE invades the substrate after the corrosion resistance test, respectively.

[0065] Depend on Figure 3-5 It can be seen that, under the experimental conditions, the alloy material of Example 1 of the present invention did not show the phenomenon of serious dissolution of alloy elements in LBE, invasion of LBE into the alloy matrix, or failure of the protective oxide layer on the alloy surface.

[0066] Figure 6 Schematic diagram of the protection principle of the product of Example 1 at different corrosion stages under LBE corrosion.

[0067] Depend on Figure 6 As shown in (a) and (b), in the early stage of corrosion, a small amount of dissolved oxygen in LBE tends to migrate and diffuse to the surface of MoAlB spontaneously, but due to the preferential oxidation of Al, a thin layer of aluminum oxide will form on the surface of MoAlB, thus playing a protective role. As time goes by, after the Al on the surface is exhausted, a Mo-rich oxide layer will form under the aluminum oxide layer ( Figure 6 (c) in the figure.

[0068] (4) In order to study the corrosion mechanism of the MoAlB alloy material of Example 1 in LBE, the present invention uses density functional theory (DFT) to calculate the substitution energy (ΔE) of Pb and Bi elements replacing Al atoms in the MoAlB lattice and the formation enthalpy (ΔH) of the substituted compounds. The calculation method is as follows.

[0069] The Al in the MoAlB unit cell is replaced by Pb or Bi with different stoichiometric ratios (x). The ΔE is calculated as follows:

[0070]

[0071] in is the total energy after Pb or Bi replaces Al in the MoAlB unit cell (LM = Pb or Bi), E Al is the energy of Al atom in stable single substance, E MoAlB is the total energy of MoAlB, E LM is the energy of Pb or Bi atom in a stable single substance.

[0072] The calculation formula for formation enthalpy (ΔH) is as follows:

[0073]

[0074] Among them, E ES is the energy of the most stable competitive phase. The test results are as follows Figure 7 shown.

[0075] Figure 7 is the substitution energy of Pb and Bi elements replacing Al atoms in the lattice of the MoAlB alloy material of Example 1 and the formation enthalpy of the substitution compound. Wherein, (a) is the substitution energy; (b) is the formation enthalpy.

[0076] Depend on Figure 7 It can be seen that within a wide range of stoichiometric ratios, the substitution energy ΔE of Pb or Bi replacing Al is positive, and the formation enthalpy ΔH of the corresponding substitution compound is also positive, which means that the reaction of Pb and Bi replacing Al in the alloy is difficult to complete spontaneously. This discovery reveals that it is difficult for Pb and Bi to replace Al in the MoAlB lattice to form chemical reaction corrosion, thus forming the thermodynamic basis for MoAlB to resist LBE corrosion.

[0077] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. Application of a MoAlB alloy material in a nuclear reactor coolant system, characterized in that: The chemical components in the MoAlB alloy material are calculated by weight: Mo 45-55 parts, Al 25-35 parts and B 5-8 parts; The preparation method of the MoAlB alloy material comprises the following steps: The elements are mixed in proportion, smelted, and an ingot is obtained; Performing heat treatment and mechanical forming treatment on the ingot to obtain the MoAlB alloy material; The coolant type in the nuclear reactor coolant system is liquid lead-bismuth eutectic.

2. The use according to claim 1, characterized in that: In the MoAlB alloy material, the mass percentage of P is ≤0.001%, the mass percentage of S is ≤0.002%, and the mass percentage of O is ≤0.002%.

3. The use according to claim 1, characterized in that: The smelting temperature is 1200-1500° C. and the smelting is carried out under a protective atmosphere.

4. The use according to claim 1, characterized in that: The heat treatment temperature is 800-1000° C. and the time is 1-5 hours.

5. A nuclear reactor coolant system, characterized in that: The cooling pipe and / or heat exchanger in the nuclear reactor coolant system is prepared using the MoAlB alloy material in the application according to any one of claims 1 to 4 as raw material.

Citation Information

Patent Citations

  • AU1210670A